A multimodal perspective on adult learners’ vocabulary explanations in the beginner-level L2 classroom - Janin, Loanne (My University, 2023)
Following the current research in conversation analysis in the field of second language (L2) learning, the present study demonstrates that beginner-level adult learners actively contribute to vocabulary explanation sequences by mobilising multimodal resources including depictive gestures, gaze, and short verbal turns. The data consist of video-recordings of whole-class interactions in a beginner-level L2 French classroom for adults with migrant backgrounds. The analysis shows how the depictive gestures deployed by learners serve either to represent concrete words, directly depicting the target item, or, combined with a short verbal explanation, to make more abstract concepts visible by contextualising the target word and associating it with a larger context of use. The findings contribute to a deeper understanding of the functioning of vocabulary explanations in the L2 classroom and, in particular, of the specific participatory dynamics in language classes for beginner-level adult learners.
Keywords: vocabulary explanation; depictive gesture; adult L2 learners; multimodal conversation analysis